Shepherding sub-Saharan Africa’s terrestrial biodiversity through peak anthropogenic pressure toward a green anthropocene - Lindsay, P.A.; Anderson, SH; Dickman, A; Gandiwa, P; Harper, SH; Morakinyo, AB; Nyambe, N; O’Brien-Onyeka, M; Packer, C; Parker, AH; Robson, AS; Ruhweza, A; et al. (Annual Reviews, 2022)
Sub-Saharan Africa’s (SSA’s) iconic biodiversity is of immense potential global value but is jeopardized by increasing anthropogenic pressures. Elevated consumption in wealthier countries and the demands of international corporations manifest in significant resource extraction from SSA. Biodiversity in SSA also faces increasing domestic pressures, including rapidly growing human populations. The demographic transition to lower fertility rates is occurring later and slower in SSA than elsewhere, and the continent’s human population may quadruple by 2100. SSA’s biodiversity will therefore pass through a bottleneck of growing anthropogenic pressures, while also experiencing intensifying effects of climate change. SSA’s biodiversity could be severely diminished over the coming decades and numerous species pushed to extinction. However, the prospects for nature conservation in SSA should improve in the long term, and we predict that the region will eventually enter a Green Anthropocene. Here, we outline critical steps needed to shepherd SSA’s biodiversity into the Green Anthropocene epoch.